Karakteristik dan Landasan Hukum Pasar: Analisis Efistimologis dan Metodologis Hukum Ekonomi Syariah - Royani, Royani; Athoillah, Mohamad Anton (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
his study intends to explore and examine the concept of the market from the perspective of Islamic teachings, both epistemologically and methodologically which have been practiced in the past. The method used in this research is descriptive analysis with a qualitative research type with a literature study approach. The results of this study prove that Islamic teachings have applied the market concept which includes foundations and characteristics as parameters and references in market governance, price setting, which avoid usury, gharar, maisir. The existence of the market has an important position in human life and life in general, so that Islamic doctrine provides a constructive and complementary basic reference as an effort to clean up the process of transferring property rights and goods from just, civilized and prosperous social relations. Keywords: Characteristics, Foundation, Market, Sharia Economic Law